Actio Pauliana Sebagai Bentuk Perlindungan Hukum Bagi Kreditor Konkuren dalam Kepailitan - Gwyneth Maylaffasya Gosal; Wenly R. J. Lolong; Henry N. Lumenta (Wajah Hukum, 2026)
Bankruptcy is a situation in which a debtor is declared unable to fulfill their debt obligations to their creditors. In this situation, creditors, especially concurrent creditors, are often in a weak position because they have no security rights over the debtor's assets. To protect their interests, bankruptcy law provides the Actio Pauliana mechanism, which is the right of the trustee or creditor to cancel the debtor's legal actions that are detrimental to creditors before the debtor is declared bankrupt. This study uses a normative legal method with an approach to relevant legislation and legal doctrine. The results show that Actio Pauliana serves as a means of legal protection for concurrent creditors so that assets that have been transferred illegally can be returned to the bankruptcy estate to be used in the fair repayment of debts. This mechanism also has a preventive function to prevent debtors from committing fraud prior to bankruptcy. However, the implementation of Actio Pauliana still faces obstacles, including proving intent to harm creditors, time limits for filing, and the weak position of concurrent creditors compared to separate and preferential creditors. Thus, the application of Actio Pauliana is an important instrument in realizing the principles of justice and equality in bankruptcy law in Indonesia.